A fatigue limit evaluation method based on plastic strain incremental energy dissipation theory. (14th April 2023) - Zu, Ruili; Zhu, Yingbin; Huang, Xianfu; Huang, Yao; Zhou, Yizhou; Zhao, Jiaye; Liu, Zhanwei
Highlights: In this paper, the plastic strain incremental energy dissipation theory (PSIEDT) is proposed, and a general expression for the fatigue limit is given with the plastic strain increment as the starting point. Combined with infrared thermal imaging and digital image correlation methods, the temperature field and deformation field were obtained synchronously, and the fatigue limit was evaluated using the plastic strain incremental energy dissipation theory. The energy dissipation in the local damage region is higher, so the fatigue limit measurements obtained with the developed method are more accurate. At the microscopic level, the onset of plastic strain corresponds to the change in the material's microstructure from reversible deformation (viscoelasticity) to permanent deformation (plasticity). This method is simpler and faster to obtain fatigue limits than traditional experimental methods, and uses fewer samples. Compared with infrared thermography, this method has wider applicability because of the limited heat release of many materials. Abstract: Metallic materials frequently undergo fatigue failure during long-term service. Therefore, the study of fatigue performance detection methods with high precision and wide application ranges is crucial to reduce fatigue failures and accidents of materials and structures. In this study, a plastic strain incremental energy dissipation theory (PSIEDT) is established, and a general expression for fatigue limit is derived with the starting point of the plastic strain increment. Taking 42CrMo4 steel as an example, and its temperature and deformation fields are obtained synchronously using infrared thermal imaging and digital image correlation. Its fatigue limit is evaluated using the energy dissipation theory based on the plastic strain increment. The results show that the relative error between the fatigue limit measurement accuracies of the developed method and the method proposed by Luong is 1.64 %. The relative error of the fatigue limit obtained for the local damage region is only 0.18 %, which has a high measurement accuracy. At the microscopic level, the onset of plastic strain corresponds to a change in the microstructure of the material from reversible deformation (viscoelastic) to permanent deformation (plasticity). Therefore, the strain measurements have higher sensitivity than the temperature measurements. Considering the limited heat release of many materials, the new method has a wide application range, can rapidly obtain material fatigue properties, and has good engineering application prospects.